Planning and licensing for marine aquaculture - Lynne Falconer; Karl Cutajar; Amalia Krupandan; Elisa Capuzzo; Richard A. Corner; Tim Ellis; Keith Jeffery; Eirik Mikkelsen; Heather Moore; Francis X. O'Beirn; Pauline O'Donohoe; Neil M. Ruane; et al. (Reviews in Aquaculture, 2023)
Marine aquaculture has the potential to increase its contribution to the global food system and provide valuable ecosystem services, but appropriate planning, licensing and regulation systems must be in place to enable sustainable development. At present, approaches vary considerably throughout the world, and several national and regional investigations have highlighted the need for reforms if marine aquaculture is to fulfil its potential. This article aims to map and evaluate the challenges of planning and licensing for growth of sustainable marine aquaculture. Despite the range of species, production systems and circumstances, this study found a number of common themes in the literature; complicated and fragmented approaches to planning and licensing, property rights and the licence to operate, competition for space and marine spatial planning, emerging species and diversifying marine aquaculture production (seaweed production, Integrated Multi‐Trophic Aquaculture [IMTA], nutrient and carbon offsetting with aquaculture, offshore aquaculture and co‐location and multiuse platforms), and the need to address knowledge gaps and use of decision‐support tools. Planning and licensing can be highly complicated, so the UK is used as a case study to show more detailed examples that highlight the range of challenges and uncertainty that industry, regulators and policymakers face across interacting jurisdictions. There are many complexities, but this study shows that many countries have undergone, or are undergoing, similar challenges, suggesting that lessons can be learned by sharing knowledge and experiences, even across different species and production systems, rather than having a more insular focus.

Multi‐stakeholder perspectives on spatial planning processes for mariculture in the Mediterranean and Black Sea - Richard A. Corner; José Aguilar‐Manjarrez; Fabio Massa; Davide Fezzardi (Reviews in Aquaculture, 2020)
Aquaculture provides more than half of the fish used for human consumption, contributing to food security and nutrition, economic growth and improved livelihoods. Aquaculture production in countries bordering the Mediterranean and Black Sea has grown steadily, though not homogenously, mainly based on marine species. To boost development, there is a need to support governance to establish activities within a coordinated spatial planning process. Knowledge of aquaculture spatial planning processes are assessed through consultations with stakeholders from 21 countries using a structured questionnaire, internal review and a workshop to determine major barriers to the implementation in the region. Results suggest different levels of knowledge of regulatory systems in the countries surveyed. Aquaculture zoning is widespread. Site selection is a long and inefficient process, a barrier to investment, exacerbated by an apparent lack of a clear distribution of power and responsibilities. Area management is the least implemented part of the spatial planning process, with few examples of an integrated approach. Poor social acceptance of aquaculture, low technical knowledge and understanding of spatial planning concepts, and a lack of meaningful communication are among the problems highlighted by stakeholders. Although recent advances are evident, the integration of aquaculture with other users of marine space remains a work in progress that requires a specific regulatory framework, capacity building, transparency, good communication and participatory processes. Application of spatial planning following an ecosystem approach to aquaculture can contribute to improvements that have the potential to counter the negative externalities of unplanned or uncoordinated development.